2010 IEEE International Conference on Data Mining 2010
DOI: 10.1109/icdm.2010.31
|View full text |Cite
|
Sign up to set email alerts
|

Training Conditional Random Fields Using Transfer Learning for Gesture Recognition

Abstract: Recently, combining Conditional Random Fields (CRF) with Neural Network has shown the success of learning high-level features in sequence labeling tasks. However, such models are difficult to train because of the increase of the parameters to tune which needs enormous of labeled data to avoid overfitting. In this paper, we propose a transfer learning framework for the sequence labeling task of gesture recognition. Taking advantage of the frame correlation, we design an unsupervised sequence model as a pseudo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…STTL is the process in which the source domain labels are available but the target is not, this is the validation stage in this study, when a calibrated model is benchmarked on further unknown data during application of a calibrated model. Transfer learning is the process of knowledge transfer from one learned task to another (Zhuang et al 2019), in this study, it is shown to be difficult to generalise a model to new subjects and thus application of a model to new data is considered a task to be solved by transfer learning; transfer learning often shows strong results in the application of gesture classification in related state-of-the-art works (Liu et al 2010;Goussies et al 2014;Costante et al 2014;Yang et al 2018;Demir et al 2019).…”
Section: Emg Gesture Classification and Calibrationmentioning
confidence: 96%
“…STTL is the process in which the source domain labels are available but the target is not, this is the validation stage in this study, when a calibrated model is benchmarked on further unknown data during application of a calibrated model. Transfer learning is the process of knowledge transfer from one learned task to another (Zhuang et al 2019), in this study, it is shown to be difficult to generalise a model to new subjects and thus application of a model to new data is considered a task to be solved by transfer learning; transfer learning often shows strong results in the application of gesture classification in related state-of-the-art works (Liu et al 2010;Goussies et al 2014;Costante et al 2014;Yang et al 2018;Demir et al 2019).…”
Section: Emg Gesture Classification and Calibrationmentioning
confidence: 96%
“…A set of labeled words in the source and target data is shared so as to build a word classifier for a new signer on a set of unlabeled target words. A transfer learning method for conditional random fields is implemented to exploit information in both labeled and unlabeled data to learn high-level features for gesture recognition by Liu et al (2010). More recently, the ChaLearn Gesture Competition (Guyon et al, 2013) provided a benchmark of methods that apply transfer learning to gesture recognition.…”
Section: Related Workmentioning
confidence: 99%
“…Em [14],é proposto um novo método baseado na estratégia de Aprendizado por Transferência, em Redes Neurais Artificiais e em Campos Condicionais Aleatórios, para reconhecimento de padrões no contexto de gestos feitos com os olhos e gestos feitos com a cabeça. A ideia apresentada pelos autoresé criar um modelo que analisa sequências de frames de vídeo de forma não supervisionada, capturando informações referentes as dependências entre os frames; essa tarefaé considerada como uma tarefa auxiliar.…”
Section: Trabalhos Correlatosunclassified